On the Stability of Steroids upon Gamma and E-Beam Irradiation and the Protective Effect of Inert Conditions - Quinten Speleers; Anke Meyers; Homaira Rashid; Yannick Dubbelboer; Elias Vanneste; Bart Croonenborghs; Annick Gillet; Aaron DeMent; Ann Van Schepdael; Erik Haghedooren (Molecules)
The sterility of ophthalmic drugs is a fundamental requirement for ensuring patient safety, and as such, it is subject to stringent regulatory standards. However, significant gaps remain regarding the effect of sterilization techniques on the impurity profile and relative content of active pharmaceutical ingredients (API). Previous research involving a set of five APIs used in ophthalmic preparations (dexamethasone, methylprednisolone, aciclovir, tetracycline hydrochloride, and triamcinolone) demonstrated that gamma irradiation led to the formation of specific impurities in the corticosteroids, dexamethasone and methylprednisolone. This study aims to further explore the effect of both gamma and electron beam (E-beam) irradiation on the impurity profiles of these APIs under varying conditions, with and without dry ice. The analyses were conducted using high-performance liquid chromatography with ultraviolet/visible light (UV/VIS) detection and the effect of sterilization conditions was assessed in accordance with the assay and related substances test outlined in the European Pharmacopoeia (Ph. Eur.). Additionally, this study investigated whether exposure in a controlled atmosphere with reduced oxygen or water content could mitigate the formation of impurities and influence the stability of the compounds. The results indicated a protective effect of low-temperature and low-oxygen environments during both gamma and E-beam irradiation but no effect of dry conditions.